The Japanese Banking Crisis of the 1990's : Sources and Lessons - Woo, David; Kanaya, Akihiro (Washington, D.C. : International Monetary Fund, 2000)
For a large part of the past decade, Japan has witnessed a steady deterioration in the health of its banking system. This paper examines what went wrong and why it has taken so long for the system to recover. While the paper traces the roots of the crisis to accelerated deregulation and deepening of capital markets without an appropriate adjustment in the regulatory framework, it identifies weak corporate governance and regulatory forbearance as the two factors behind what might have been an unnecessary prolongation of the distress of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet